Condiciones de vida e indicadores de bien-estar y pobreza en el municipio de Pasto. Línea base de la zona urbana 2008 - Ortiz, Robert Wilson; Hidalgo Troya, Arsenio; Riascos, Julio César; Bastidas Tapia, Diana (Universidad y Salud, 2009)
People’s life and welfare conditions were studied based on the homes´ social survey applied in the urban zone in the municipality of Pasto. This survey was carried out by the investigation group “Coyuntura Social” taking into account the calculation of the Relative Poverty Index, the Unsatisfied Needs Index (NBI), Living Conditions Index (ICV) and the Gini’s coefficient and considering general characteristics related to the size of the household and typology and home´s boss according to the sex. Moreover, the housing quality, its physical structure, the tenure and access to basic services were considered, along with the families’ level of income and expenses study because it is an important element in this type of analysis. The document shows the indicators situation both for the population in general and for each particular strata of the city.